Proceedings of the 2014 Zone 1 Conference of the American Society for Engineering Education 2014
DOI: 10.1109/aseezone1.2014.6820632
|View full text |Cite
|
Sign up to set email alerts
|

WolfBot: A distributed mobile sensing platform for research and education

Abstract: Mobile sensor networks are often composed of agents with weak processing capabilities and some means of mobility. However, recent developments in embedded systems have enabled more powerful and portable processing units capable of analyzing complex data streams in real time. Systems with such capabilities are able to perform tasks such as 3D visual localization and tracking of targets. They are also well-suited for environmental monitoring using a combination of cameras, microphones, and sensors for temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…As such, there is a large body of work addressing key application areas: bio-inspired systems [6], coordination [15], task-allocation [27], communication [11], localization and mapping [30] and control approach [9], just to name a few. Reviews on multi-agent research areas for swarm robotics can be found in [19] [37] and a more recent review on swarm robotics multi-agent engineering can be found in [28]. In order to support the requirements of these multirobot systems the individual robot designs are task centric [5] [7][13] [16] [25] or make tradeoffs between: cost, modularity, size, processing power, energy consumption, versatility of sensory systems and communication capabilities, robustness , ease of use and monitoring [1][2][3][4] Early work on mobile robot designs used in swarm robotics research and education was done by Mondada et al [1].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, there is a large body of work addressing key application areas: bio-inspired systems [6], coordination [15], task-allocation [27], communication [11], localization and mapping [30] and control approach [9], just to name a few. Reviews on multi-agent research areas for swarm robotics can be found in [19] [37] and a more recent review on swarm robotics multi-agent engineering can be found in [28]. In order to support the requirements of these multirobot systems the individual robot designs are task centric [5] [7][13] [16] [25] or make tradeoffs between: cost, modularity, size, processing power, energy consumption, versatility of sensory systems and communication capabilities, robustness , ease of use and monitoring [1][2][3][4] Early work on mobile robot designs used in swarm robotics research and education was done by Mondada et al [1].…”
Section: Related Workmentioning
confidence: 99%
“…Communication and sensing is limited and is accomplished through a single IR sensor. Wolfbot [28] is another low cost robot design ($550 in parts) with an approximate diameter of 178 mm that is built around the popular Beaglebone embedded board [32]. The design incorporates an accelerometer, a vision sensor with integrated microphone, 5 IR sensors and wireless communication.…”
Section: Related Workmentioning
confidence: 99%
“…On the other hand, small-scale robots, especially micro robots that are usually employed in the swarm robotic research, can hardly benefit from visual sensing. Even though the growth of interest in swarm robotics has brought us a wide range to choose from [2][3][4][5][6], there is still no optimal design for all desires. One of the greatest challenges is the trade-off between limited computational resources on-board and the requirements for image processing in real-time.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the E-puck [2], Swarm-bot [3] or mROBerTO [4] are short of RAM size or sufficient CPU frequency. On the other hand, for those robots whose CPU are strong enough, they are usually oversized for swarm scenarios, such as Kobot [5], Wolfbot [6] and Khepera III. The comparison of related robot platform are illustrated in table 1.…”
Section: Introductionmentioning
confidence: 99%
“…The WolfBot [10] is an open source platform designed for distributed sensing and education. It has a sensor suite for communication, localization, and on-board image processing.…”
Section: Existing Platformsmentioning
confidence: 99%